PENGARUH TATA LETAK INSTRUMEN GAMELAN JAWA DI PANGGUNG PENDHAPA ISI SURAKARTA TERHADAP PARAMETER AKUSTIK BAGI PENGENDANG - -, Suyatno (Instrumentasi, 2013)
This paper is discussed an analysis of the acoustics parameters of Javanese Gamelan instruments layout at position of performer namely Pengendang (drummer). This is of importance as in the Gamelan concert, Pengendang is a performer who frequently acts as 'a conductor' (leader) of the performance. As a leader, Pengendang has a duty to maintain the rhythm and tempo of the performance based on the perceived tones as result of Pengendangâ€™s left and right ear response (IACC). Pengendang realizes such a duty by giving a direction through tones produced by the â€œkendangâ€. The tones produced by the gamelan lead to particular characteristics of the sound field. Theoretically, the sound field produced by each instrument of the gamelan that is affected by the space properties where the performance is being conducted. In this research, Pendhapa ISI Surakarta was considered as the stage in which the Javanese Gamelan was performed. The Pendhapa 'ISI Surakarta' is a semi-outdoor concert hall. Therefore, this produces a direct sound to the receiver particularly for the performers. It is found that the acoustics parameters measured at Pengendang position for gending "Gambyong Pareanom" is 98 dB for Listening Level (LL) while Tau-e and tau-1 are 24.9 ms and 2 ms respectively. IACC of 0.81 is also pronounced. These values indicate that the Javanese gamelan performed in Pendhapa ISI Surakarta has particular acoustic characteristic. However, this acoustic charactertics has not yet been â€œoptimum acoustics preferenceâ€ as expected by a drummer. Therefore, it is instructive to investigate this further based on fisio- and physio- acoustic aspecs in order to ensure communication among the performers through the tones can be maintained. Keywords: Javanese Gamelan, instruments layout, Pendahpa, Pengendang, Listening Level, Tau-e, Tau-1, IACC.